English in contemporary Iran. Issue 1 (2nd January 2018) - Zarrinabadi, Nourollah; Mahmoudi-Gahrouei, Vahid
Abstract: As a part of the Expanding Circle in the concentric model of the Englishes around the world, English plays an important function in various domains in contemporary Iran. While English does not have any recognized official status in the country, it is widely used in education, business discourse, and media. This article discusses the sociolinguistic characteristics of Iran, reviews the use and the status of different foreign languages in the country, and elaborates on the functions of English in present-day Iran. The article also considers that further spread of English in various aspects of the everyday lives of Iranian people has been influenced by the mass media and the increasing use of the Internet and social networks.